Field Observation and Theoretical Study on an Existing Tunnel Underpassed by New Twin Tunnels - Qiongfang Zhang (Advances in Civil Engineering)
The methodology of the existing displacement control is illustrated taking the shield of twin tunnels of Line 4 underpassing the upline tunnel of existing metro Line 1, for example. Vertical, horizontal, and convergence displacement of the existing tunnel is monitored and analyzed in detail in this paper. Shield parameters are predefined and adjusted based on the feedback of the displacement of Line 1. Short-term displacement of the existing tunnel is greatly influenced by the relative distance between the shield face and the existing tunnel and shield parameters. The shapes of horizontal and convergence displacement curves are similar. Line 1 is reinforced, and a new analysis method is firstly proposed for the design of reinforcement of the existing tunnel which is verified by the analytical methods derived from prior studies. The results show that the change of reinforcement stiffness has a greater effect on the normalized bending moment and the normalized shear force of the existing tunnel, and reinforcement of 25 rings on either side of the intersection point is the best choice in this case. The proposed model can be widely applicable for reinforcement design and safety check of the existing tunnel.